Pemanfaatan Air Hujan Untuk Sistem Pemadam Kebakaran Hidran Dan Sprinkler Pada Gedung Kantor Wilayah I Bank Tabungan Negara Kota Bandung - Utami, Alia Putri; Aini, Nadia Nur; Karnisah, Iin; Permana, Rahmat (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Office buildings require security systems to ensure comfort, such as fire protection systems, including adequate water supply. This research implements rainwater harvesting as an alternative source for more efficient water resource management and modifies the piping system for hydrants and sprinklers. In this study, a hydrological analysis was conducted based on rainfall data in Bandung City from 2014 to 2024, assessing the water needs for hydrants and sprinklers, as well as analyzing the plans for filtration, pumping, and storage tanks for the rainwater harvesting system. This research utilizes a storage tank with a capacity of 128 m³ and employs Nanotec filtration using FRP filter media, along with a pump capacity of 125-139 m, operating on power ranging from 110-132 kW. The results of the study indicate that the availability of harvested rainwater reaches 55% of the requirements for hydrants and sprinklers.